Pendampingan Strategi Pemasaran dan Desain Kemasan Pada Produk Olahan Kacang Hijau Goreng UMKM Risma Kacang Hijau Goreng - Pipin Fitriasari; Anisa Ahmad; Azizah Safina; Megah Puspita (Kegiatan Positif : Jurnal Hasil Karya Pengabdian Masyarakat, 2024)
The mentoring activities carried out in community service are specifically for Micro, Small and Medium Enterprises (MSMEs) in Balikpapan City, Klandasan Ilir Village. The target of MSMEs targeted in this mentoring activity was carried out at MSME Risma Kacang Hijau Goreng RT.14 Klandasan Ilir Village,Balikpapan Kota. The activities carried out include digital marketing strategies, product design and providing entrepreneurial knowledge. The results of this mentoring activity, Risma's MSME, Fried Green Beans, was able to implement marketing strategies and create product packaging designs in managing its business.